The SIAMESE family of cell-cycle inhibitors in the response of plants to environmental stresses - Braat, Jeanne; Havaux, Michel (Frontiers in Plant Science, 2024)
Environmental abiotic constraints are known to reduce plant growth. This effect is largely due to the inhibition of cell division in the leaf and root meristems caused by perturbations of the cell cycle machinery. Progression of the cell cycle is regulated by CDK kinases whose phosphorylation activities are dependent on cyclin proteins. Recent results have emphasized the role of inhibitors of the cyclin-CDK complexes in the impairment of the cell cycle and the resulting growth inhibition under environmental constraints. Those cyclin-CDK inhibitors (CKIs) include the KRP and SIAMESE families of proteins. This review presents the current knowledge on how CKIs respond to environmental changes and on the role played by one subclass of CKIs, the SIAMESE RELATED proteins (SMRs), in the tolerance of plants to abiotic stresses. The SMRs could play a central role in adjusting the balance between growth and stress defenses in plants exposed to environmental stresses